Innovationism between Art and Technology: Technological determinism in the controversy around Vantablack - Campagnaro, Yuri Gabriel (NOvation — Critical Studies of Innovation, 2025)
This article investigates how innovationism—the neoliberal paradigm framing technological innovation as a profit-driven imperative—structures the sociotechnical controversy surrounding Vantablack. Through an STS lens, we analyze how Surrey NanoSystems, Anish Kapoor, and Stuart Semple mobilize contradictory narratives that simultaneously critique and reproduce innovationist ideologies. While the material’s development as a nanotechnology-based "superblack" pigment exemplifies technological determinism (treating Vantablack’s emergence as an autonomous scientific breakthrough), its artistic appropriation reveals co-produced tensions between market logics and cultural production. The actors’ practices demonstrate innovationism’s paradoxes: Surrey NanoSystems oscillates between high-tech branding and low-end commercialization; Kapoor leverages exclusivity despite achieving similar aesthetic effects through conventional means; Semple’s democratizing rhetoric relies on the same novelty-seeking mechanisms he condemns. These contradictions emerge from a shared ideological framework that naturalizes innovation as both economically necessary and socially neutral, obscuring its role in reinforcing asymmetries of access and power. We argue that the Vantablack controversy crystallizes broader tensions in technoscientific governance, where innovationism mediates between art, technology, and politics. Rather than resolving these tensions, the case exposes how even competing positions remain constrained by market-centric epistemologies that privilege short-term profitability over collective benefit. The study advances critical perspectives on innovation by unpacking its material, discursive, and ideological dimensions in contested cultural domains.